Studi Literatur: Pengaruh Konsumsi Junk Food terhadap Obesitas: Literature Review: Effect of Junk Food Consumption on Obesity - Lelia Pebriani; Agnes Frethernety; Elsa Trinovita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Data based on the World Health Organization (WHO) in 2018 shows that 650 million people in the world suffer from obesity. Indonesia is a country that ranks 4th in Southeast Asia with 14.3% of obesity cases. One of the factors that causes the increase in obesity is the consumption of junk food. However, there are differences in research results regarding the effect of junk food consumption on obesity in terms of the frequency of junk food consumption. The purpose of this literature review is to determine the effect of the frequency of consumption of junk food on obesity when studied scientifically. This literature review research uses a systematic review approach. Sources of research data using secondary data include scientific journals that meet the inclusion and exclusion criteria. Based on the synthesis of data from 15 journals studied, there are 13 journals which state that consumption of junk food has an effect on obesity, and 2 journals which state that it does not have an effect of consumption of junk food on obesity. Most obese patients have leptin resistance, which will make leptin levels high so that it does not cause a decrease in appetite.